Physics Learning Design of Faraday's Induction Law Material Using PhET Simulation (Department of Physics, Faculty of Mathematics and Natural Sciences, 2019)
The purpose of this research is to make a learning design on Faraday’s Induction Law using a PhET Faraday’s Electromagnetic Lab simulation and to investigate the effectiveness of the design on students' understanding. Descriptive research was used as the method of this research. The instruments of this research were the observation sheet on students' attitudes and learning activities, questionnaires, and cognitive evaluation test questions. There were 14 students of grade IX of a Junior High School in Salatiga as the respondents of this research. The data collected from the research instruments were then analyzed using the descriptive qualitative technique. Based on data analysis of the observation results of learning activities, students' attitudes, questionnaires, and cognitive evaluation test scores; the results showed that the learning design for Faraday’s Induction Law using the PhET simulation of Faraday's Electromagnetic Lab was effective to help students understand the Faraday's Induction Law.